Formyl Peptide Receptor 1 and 2 Dual Agonist Inhibits Human Neutrophil Chemotaxis by the Induction of Chemoattractant Receptor Cross-desensitization - Yoshitaka Sogawa; Takao Ohyama; Hiroaki Maeda; Kazuki Hirahara (Elsevier, 2011)
Formyl peptide receptor 1 (FPR1) and FPR2/ALX are known to control neutrophil chemotaxis in response to various ligands. In this study, we investigated the inhibitory mechanism of compound 43 (Cpd43), an FPR1 and FPR2/ALX dual agonist, on human neutrophil chemotaxis. Precedent stimulation of human peripheral blood neutrophils with Cpd43 rendered the cells unresponsive in calcium mobilization induced by interleukin-8, C5a, or leukotriene B4. In addition, neutrophils pretreated with Cpd43 lost their chemotactic responses against these chemoattractants, wherein the expressions of chemoattractant receptors CXCR1, CXCR2, C5a receptor, and leukotriene B4 receptor 1 on the surface of neutrophils were all diminished significantly by treatment with Cpd43. By evaluating its pharmacological effect on 341 molecules, including receptors and enzymes, we also confirmed that Cpd43 has a highly specific affinity to FPR1 and FPR2/ALX and does not show binding affinity to the other chemoattractant receptors. These results indicate a previously unrecognized inhibitory mechanism of Cpd43 on neutrophil chemotaxis: the induction of cross-desensitization of multiple chemoattractant receptors in human neutrophils through its FPR1 and FPR2/ALX dual agonism. Keywords:: formyl peptide receptor, neutrophil, chemotaxis, cross-desensitization